2021
DOI: 10.34172/hpp.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Peoples’ attitude toward COVID-19 vaccine, acceptance, and social trust among African and Middle East countries

Abstract: Background: To end the COVID-19 pandemic, a large part of the world must be immune to the virus by vaccination. Therefore, this study aimed to gauge intent to be vaccinated against COVID-19 among ordinary people and to identify attitudes towards vaccines and barriers for vaccine acceptance. Methods: The study population comprises 1880 people residing in different countries that answer a prepared questionnaire. The questionnaire topics are demographics, historical issues, participants’ attitudes and beliefs reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…On the other hand, data obtained from healthcare workers from six Asian countries shows very low hesitancy among this population, with a high 95% acceptance rate [106] . Finally, a diverse study conducted among people from 42 African and Middle East countries found that up to one third of the participants did not have the intention to receive the vaccine [107] . Europe …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, data obtained from healthcare workers from six Asian countries shows very low hesitancy among this population, with a high 95% acceptance rate [106] . Finally, a diverse study conducted among people from 42 African and Middle East countries found that up to one third of the participants did not have the intention to receive the vaccine [107] . Europe …”
Section: Resultsmentioning
confidence: 99%
“…Previous research examining vaccine attitudes indicated geographical disparities in perceptions of vaccination’s safety and efficacy. Addressing vaccine hesitancy in a particular population may be necessary due to the phenomenon’s complex features [ 19 , 20 ]. It is critical to understand the factors of intention to acquire COVID-19 immunization among Indonesian HCWs since these variables may vary significantly by region, culture, and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Large parts of the world are unfortunately still waiting for the chance at a first vaccine shot. To ensure maximal vaccine uptake healthcare providers and policy makers should provide enough information on vaccine safety, individual risk assessment and explicitly recommend vaccination as support from healthcare providers increases chance of vaccination ( 33 , 34 , 36 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%